An Analysis of Cultural in Selected English Textbooks for Junior High School - Noor, Pajrian (Intensive Journal, 2024)
The cultural textbook analysis in this study utilized an English junior high school textbook, which was authored by the Indonesian Ministry of Education and Culture. The examination of textbook contents holds significant importance, as it has been observed that certain junior high school educators in Indonesia may rely solely on instructional materials without conducting thorough research or considering potential cultural allusions.  In addition to this, the integration of other cultures such as the local or indigenous culture, the target culture, and the global culture within textbooks enables students and educators to acquire knowledge about diverse cultural perspectives alongside the English language. This study seeks to provide an answer to the following query based on the study's Introduction that was just presented: What is the distribution of cultural in the following textbooks? The results show that the three textbooks for grade VII-IX present multicultural integration from the three culture categories. The percentage of cultures in each textbook was not balanced. It can be seen in the first textbook for Grade VII that the source culture was 54%; International culture having 38% and the target culture was 7%. Moreover, the second textbook which is for Grade VIII presented that the international culture was presented more than the other types of culture. The percentage was 60%, which means the global culture played higher than the source culture having 22% and the target culture with only 18%. On the third textbook which is   for Grade IX displayed source culture having 59% which means that the Indonesian culture was presented exhaustively over the international culture, with only 32%, and the target culture was 9%.